Genetic diversity of Lombok chickens based on D-loop mitochondrial DNA sequences - Arifin Zein, M. Syamsul; Sulandari, Sri (Indonesian Animal Sciences Society, 2008)
Mitochondrial DNA (mtDNA) displacement (D)-loop sequences were used to study the genetic diversity and relationship of Lombok chickens. A total of 45 individuals were sampled. The D-loop segment was PCR amplified and subsequently sequenced. The sequences of the 785 nucleotides were used for analysis. Twelve haplotypes were identified from 25 polymorphic sites with polymorphism between nucleotides 200 and 400 contributing to 80% of the variation. Fuâs Fs value was - 8.768 (all samples, P = 0), indicating high genetic diversity and population expansion, a conclusion supported by a neighborâ joining analysis of the haplotypes. Nucleotides diversity of the Lombok chicken were 0.00221 and haplotype diversity were 0.654 + 0.08. The dominant haplotype found among the Lombok chickens was haplotype B (62%) and genetic distances value ranged from 0.001 to 0.017. Â Â Key Words: Mtdna, D-Loop, Genetic Diversity, Haplotype, Lombok Chicken